KNOWLEDGE, SKILLS, AND ATTITUDES OF MALAYSIAN STUDENT ON GLOBAL CITIZENSHIP EDUCATION - Hamidah Yusof; Mohd Asri Mohd Noor; Mahaliza Mansor; Jamal Yunus (Jurnal Cakrawala Pendidikan, 2019)
Student’s perception on the current global citizenship education might have evolved. This study aims to identify the level of knowledge, skills, and attitudes of global citizenship from students’ perceptions. It also examined the relationship between students’ knowledge with the skills and attitudes of global citizenship. This study involved 155 first semester students in a public university in Malaysia. The selection of these respondents is to get their views on the education of global citizenship they received at schools. They were chosen because they had just finished secondary schools, and their experiences were still fresh in memory. They also came from various schools in Malaysia and able to draw on the experience of global citizenship education in Malaysia. This study was quantitative and used a questionnaire as the research instrument. The findings show that the level of knowledge, skills, and attitudes of students towards global citizenship is at a moderate level. The relationship between knowledge, skill, and attitude towards global citizenship is high, positive, and significant. The multiple linear regression analysis showed that skill and attitude are the predictors for the knowledge in the students. This study implies that global citizenship education is important to equip students to understand global issues and become global citizens.